Do Islamic Bankers Optimist on Islamic Banking Growth? Case Study of Islamic Banking Employees in Indonesia - Dini Oktora Rianti; Yaser Taufik Syamlan (Tazkia Islamic Finance and Business Review, 2021)
This study aims to determine the perceptions of Islamic banking employees on the growth of Islamic banking in the future. This research is also to find out the influence of products and services, experience and skills, marketing of products and services, and practices of Islamic banking on the growth of Islamic banking. The sample used in this study was 100 respondents of Islamic banking employees in Indonesia. The method used is path analysis. The results of this study indicate that the perception of products and services has no significant and positive effect on Islamic banking practices, perceptions of experience and skills have a significant and positive effect on Islamic banking practices, perceptions of product and service marketing have a significant and positive effect on sharia banking practices, then product perceptions and services have no significant and positive effect on the growth of Islamic banking, perceptions of experience and skills have no significant and positive effect on the growth of Islamic banking, perceptions of product and service marketing have a significant and positive effect on the growth of Islamic banking, and the perception of Islamic banking practices has a significant and positive effect on growth of Islamic banking. From the results of this study, it is expected that Islamic banking employees need to improve the practice of Islamic banking in the perception of products and services. Then sharia banking employees also need to improve products and services and perceptions of experience and skills in the growth of Islamic banking. Keywords: Future Growth, Perception, Islamic Banks